National Evidence of Depth‐Dependent Stabilization and Controls of Soil Organic Carbon in Dryland Croplands - Yuchen Wei; Xin Zhao; Wenting Feng; Hongyong Sun; Jinfeng Chang; Hong Chen; Ji Chen; Xiaowei Guo; Di He; Feng Liu; Alain F. Plante; Zhou Shi; et al. (Global Change Biology, 2026)
Soil organic carbon (SOC) underpins agricultural sustainability and the terrestrial carbon cycle, yet its vertical distribution and stabilization across soil depth remain poorly constrained at large spatial scales. Here, we present a nationwide, depth‐resolved dataset of SOC and mineral‐associated organic carbon (MAOC)—the more persistent SOC fraction—from 365 dryland cropland sites across China, sampled to 2 m depth. Contrary to the classic model of exponential SOC decline, 46% of profiles exhibited uniform or increasing SOC and MAOC with depth, highlighting a substantial role of subsoil carbon. MAOC accounted for more than half of total SOC in most layers, but its relative contribution declined below 1 m, challenging the assumption that subsoil carbon is inherently more stable. Clay + silt content was the strongest predictor for SOC, MAOC, and MAOC/SOC across depths, while vegetation productivity, a proxy for carbon inputs, was positively associated with all three. The influence of clay + silt on MAOC accumulation weakened with depth, and the positive interaction between vegetation productivity and clay + silt weakened or diminished from surface soils to deeper layers. These patterns indicate a transition from joint regulation by carbon inputs and mineral surfaces in surface soils toward an increasingly input‐limited regime in deeper layers, as inferred from the depth‐dependent changes in the relative importance of vegetation productivity and fine particle content. National mapping estimated ~19.9 Pg SOC stored within the 0–2 m layer in China's dryland croplands, with 75% below 0.3 m and 60% stabilized as MAOC. These results provide a benchmark for depth‐explicit SOC accounting and highlight the importance of aligning carbon inputs with soil mineralogy to enhance whole‐profile carbon stabilization and climate mitigation.